ANALISIS PENGENDALIAN INTERNAL SIKLUS PENJUALAN EKSPOR PADA CV UNIVERSAL VINDO COCO DI SURABAYA - Elier, Elsya (J-MACC : journal of management and accounting, 2026)
This study aims to analyze the internal control system in the export sales cycle at CV Universal Vindo Coco Surabaya. Export sales activities involve high risks, including goods weight depreciation, document discrepancies, and errors due to manual financial recording, which may lead to inefficiencies and potential fraud. This study uses a qualitative descriptive approach, with data collected through observation, interviews, and documentation involving key informants such as the director, warehouse manager, quality control division, and operational staff. Data analysis was conducted by comparing the company’s practices with the COSO internal control framework, which includes control environment, risk assessment, control activities, information and communication, and monitoring. The results show that although the company has implemented internal controls, they are not yet optimal, particularly in cargo planning, depreciation recording, document archiving, and sales recording. The use of manual systems also increases the risk of data inconsistencies and document loss. Therefore, the company is recommended to strengthen its internal control system by improving procedures, enhancing employee accuracy, and adopting a digital recording system to increase efficiency and reduce risks.